Electroorganic reduction synthesis - Torii, Sigeru (Wiley - VCH, 2006)
This two-volume book presents everything you need to know about modern electroorganic reduction methods, covering all important organic substance classes, such as aldehydes, olefins, aromatic and halogenated compounds. Besides a plethora of modern reaction methods, it also treats such other important aspects as product selectivity, types of electrolysis cells and effects of additives. With its clear structure and its focus on synthetic methods, this is a source of high quality information for every chemist working in this field.